2011
DOI: 10.1002/acr.20618
|View full text |Cite
|
Sign up to set email alerts
|

Experimental knee joint pain during strength training and muscle strength gain in healthy subjects: A randomized controlled trial

Abstract: Objective. Knee joint pain and reduced quadriceps strength are cardinal symptoms in many knee pathologies. In people with painful knee pathologies, quadriceps exercise reduces pain, improves physical function, and increases muscle strength. A general assumption is that pain compromises muscle function and thus may prevent effective rehabilitation. This study evaluated the effects of experimental knee joint pain during quadriceps strength training on muscle strength gain in healthy individuals. Methods. Twenty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
5
0
1
Order By: Relevance
“…Lower extremity muscle strength was assessed by knee torque. A Biodex unit (Biodex Medical Systems) was used to measure peak isokinetic torques of knee extension and flexion at 120 degrees/second, adjusted for body weight . Participants completed 2 reproducible and acceptable trials.…”
Section: Methodsmentioning
confidence: 99%
“…Lower extremity muscle strength was assessed by knee torque. A Biodex unit (Biodex Medical Systems) was used to measure peak isokinetic torques of knee extension and flexion at 120 degrees/second, adjusted for body weight . Participants completed 2 reproducible and acceptable trials.…”
Section: Methodsmentioning
confidence: 99%
“…A Biodex® unit was used to measure peak isokinetic torques of knee extension and flexion at 120 degrees/second adjusted for body weight (34). Participants completed two reproducible and acceptable trials.…”
Section: Methodsmentioning
confidence: 99%
“…2 Several studies regarding knee OA have shown that exercise has positive effects on pain and function, and is cost-effective, and increasing muscle strength improves joint stability and reduces pain and disability. [3][4][5][6][7] On the other hand, OA affects articular cartilage, subchondral bone, synovium, and ligaments, but articular cartilage degradation, from a pathophysiological point of view, is considered to be one of the main causes of OA progression. [8][9][10] Therefore, there is concern about whether physical exercise causes further degeneration of articular cartilage, especially in elderly people.…”
Section: Introductionmentioning
confidence: 99%